Fiber crossbars: an emerging architecture of smart electronic textiles - Zhou, Xuhui (2024)
Smart wearables have a significant impact on people's daily lives, enabling personalized motion monitoring, realizing the Internet of Things, and even reshaping the next generation of telemedicine systems. Fiber crossbars (FCs), constructed by crossing two fibers, have become an emerging architecture among the accessible structures of state-of-the-art smart electronic textiles. The mechanical, chemical, and electrical interactions between crossing fibers result in extensive functionalities, leading to the significant development of innovative electronic textiles employing FCs as their basic units. This review provides a timely and comprehensive overview of the structure designs, material selections, and assembly techniques of FC-based devices. The recent advances in FC-based devices are summarized, including multipurpose sensing, multiple-mode computing, high-resolution display, high-efficient power supply, and large-scale textile systems. Finally, current challenges, potential solutions, and future perspectives for FC-based systems are discussed for their further development in scale-up production and commercial applications.